Electrocardiographic Changes after General Anaesthesia Induction in a Patient with Subarachnoid Haemorrhage and Thyroid Heart Disease: A Case Report - Sanjaya, Dewa NGD; Permana, Padma; Satyarsa, Agung BS; Wardhana, Dewa PW (Universitas Kristen Maranatha, 2025)
Electrocardiographic (ECG) abnormalities are commonly observed in patients with subarachnoid hemorrhage (SAH) and patients and are linked to worse outcomes. This case report documents the rapid normalization of severe ECG abnormalities following general anesthesia induction in a high-risk SAH patient with hyperthyroid heart disease. We report an 81-year-old woman with Fisher grade IV SAH and hyperthyroidism-associated cardiomyopathy who presented obtunded (GCS 7) with refractory atrial fibrillation at 116 bpm, diffuse T-wave inversions, and elevated troponin I. Following a multidisciplinary discussion, an External Ventricular Drain (EVD) was placed under general anesthesia using fentanyl, propofol, and rocuronium. This resulted in the immediate restoration of sinus rhythm, resolution of repolarization changes, and stabilization of blood pressure. Despite comprehensive ICU management—including analgesia, sedation, osmotherapy, steroids, and diuretics—the patient’s condition deteriorated within 24 hours, developing refractory intracranial hypertension and leading to death. This case highlights the autonomic-modulating and antiarrhythmic properties of anaesthetic agents in SAH-related neurocardiogenic dysfunction and underscores the need for further research into optimal anaesthesia strategies and patient outcomes.